MODEL PUNGUTAN PAJAK PADA MASA KUMPENI DI JAWA TIMUR - Wijayati, Putri Agus (History Department, Semarang State University and Historian Society of Indonesia, 2010)
Tax collection system in the concept of the modern colonial states was made by Raffles in 1811. But decades earlier, the implementation of natural resource charges on the population has been carried out when Kumpeni started to run